2020
DOI: 10.2478/jtim-2020-0036
|View full text |Cite
|
Sign up to set email alerts
|

Progress in endoscopic treatment of hemorrhoids

Abstract: Hemorrhoids are one of the most common diseases of the anorectal region. Previously, treatment for hemorrhoids included conservative treatment, outpatient treatment, and surgical treatment. The development of flexible reversible endoscopes has provided precise controllability and imaging, enabling further improvement and development of various endoscopic techniques to treat hemorrhoids. This article discusses several of these endoscopic techniques: rubber band ligation, sclerotherapy, and electrocoagulation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 65 publications
0
4
1
1
Order By: Relevance
“…Some studies mentioned that RBL has higher efficacy and lower recurrence19–21 but conflicted with the results we obtained. In our study, no significant difference was found between RBL and coagulation in terms of efficacy rate, and recurrence rate after treatment.…”
Section: Discussioncontrasting
confidence: 81%
“…Some studies mentioned that RBL has higher efficacy and lower recurrence19–21 but conflicted with the results we obtained. In our study, no significant difference was found between RBL and coagulation in terms of efficacy rate, and recurrence rate after treatment.…”
Section: Discussioncontrasting
confidence: 81%
“…Another potential treatment option is the application of a ligature to the hemorrhoidal artery. In the event of disease progression, surgical intervention is the definitive treatment for severe and thrombosed external hemorrhoids [26][27][28].…”
Section: Graphical Abstract Backgroundmentioning
confidence: 99%
“…Another potential risk of sclerotherapy is the development of blood clots in the treated veins, which may cause inflammation and pain. In addition, there is a risk that the injected chemical solution may leak into surrounding tissues, causing damage or irritation [42,43]. In some cases, sclerotherapy may also lead to the recurrence of hemorrhoids or the development of new hemorrhoids.…”
Section: Sclerotherapymentioning
confidence: 99%
“…Outpatient treatment is usually sufficient for patients with hemorrhoids, allowing them to leave the hospital soon after treatment. However, the effectiveness of EIS typically takes 1-2 weeks [42,44]. During this time, it is helpful for doctors and nurses to provide education and information to patients to improve treatment success.…”
Section: Sclerotherapymentioning
confidence: 99%